The Digital Divide and Gender: A Survey of Environmental Community Organizations’ Leaders in Perth, Western Australia - Dhakal, Subas P. (Journal of Community Informatics, 2010)
The digital divide is generally considered to be the lack of capability to adopt and effectively utilize Information and Communication Technologies (ICT). Although the need of building ICT capability of community organizations in Australia has been increasingly emphasized in recent years, the gender dimensions of digital divide amongst leaders of community organizations remain unexplored. This paper responds to this gap and explores the trend of ICT adoption amongst Environmental Community Organizations (ECOs) in Western Australia with a gender lens. The findings from a survey of 81 ECOs indicated that benefits and barriers associated with ICT adoption significantly differed according to gender of the leader. Drawing on the survey findings, the paper concludes by discussing why gender matters in overcoming the digital divide and makes recommendation for further research.